Upaya Peningkatan Kinerja Restoran Pondok Ciung Melalui Proses Rekrutmen Dan Seleksi Karyawan - Muchsinati, Evi Silvana; Dulfi, Saidah (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Pondok Ciung, a restaurant that has just opened a branch at King Business Centre (KBC) in Batam, is facing several operational challenges, especially in terms of human resource management. The problems that arise include inappropriate recruitment and lateness of employees in starting operational hours. Therefore, this program aims to help recruit and select new employees, analyze employee performance, implementation of new work rules, and prevent further decline in performance and lateness of employees. The output of this activity is a draft SOP. The methods used in this program include interviews, observations, and documentation. The expected results of this activity are increased recruitment quality and employee discipline, which will ultimately increase productivity and operational success of the restaurant.